Pigmented onychomatricoma: A clinical simulator that could not mislead ultrasound - Peruilh-Bagolini, Leonardo; Dossi, Maria Teresa; Wortsman, Ximena; Montero, Tabata (Acta Biomedica Atenei Parmensis, 2021)
Introduction: Onychomatricoma is a rare subungual tumor composed of stroma and nail matrix-like epithelium. Only seven cases of the pigmented variant have been reported in the literature. Case report: We present a 62-year-old male patient with a 2-years history of a single fingernail thickening, deformation, and hyperpigmentation. He had been treated for onychomycosis, without improvement. Due to the increasing hyperpigmentation, and to rule out tumoral entities, including melanoma, a color Doppler ultrasound examination of the nail was requested, which showed a hypoechoic tumor of the nail matrix and bed, with hyperechogenic linear images inside, suggesting the diagnosis of onychomatricoma. Onychectomy and partial matricectomy were performed. Histological evaluation confirmed the diagnosis of onychomatricoma. Discusion and conclusion: Histological evaluation is the gold standard for the diagnosis of onychomatricoma. However, ultrasonography represents an easily accessible, non-invasive diagnostic tool for the initial evaluation of these tumors, especially in unsuspected atypical clinical presentations.